Principle Of Legality And Its Transformation In Brazil - Zockun, Carolina; Zockun, Mauricio; Bandeira De Mello, Gabriela (Acta Universitatis Danubius. Juridica, 2022)
This article investigates the scope of the principle of legality in Brazil, its basis, developments, and limits and the role of governing officials in light of this principle. In a summarized manner, we examine the several instruments for the control of legality found in the Brazilian Constitution of 1988. We also analyze the legal institutes of a state of siege, a state of defense, and provisional measures, seeking to identify the reach of such exceptions to legality in Brazil and how their inordinate use has had an adverse effect on Brazilian society.